Accumulation of free nuclei denotes defective phagocytic capacity of macrophages and occurs after infection with Listeria monocytogenes and lymphocytic choriomeningitis virus - Christ, Theresa Charlotte; Friebus-Kardash, Justa; Bergerhausen, Michael; Elwy, Abdelrahman; Abdelrahman, Hossam; Holnsteiner, Lisa; Tertel, Tobias; Wiebeck, Elisa; Geuer, Ilka; Gerbaulet, Alexander; Lang, Philipp Alexander; Lang, Karl Sebastian (Frontiers in Immunology, 2026)
Efficient phagocytosis of pathogens is a key effector function of the innate immune system. Impaired phagocytic activity can result in uncontrolled pathogen proliferation and life-threatening infections. However, reliable methods to detect early dysfunction of the phagocytic system in vivo are limited. Here, we used a mouse model of Listeria monocytogenes infection to determine blood parameters which correlate with limited macrophage function. We found that lack of macrophages led to accumulation of nuclei in the blood. Further analysis of nuclei revealed that these nuclei were released from bone marrow-derived cells. Macrophage-depleted mice and interferon-gamma-deficient mice, which are known to have reduced phagocytotic capacity, showed increased amounts of free nuclei. This was associated with lethal outcome and occurrence of acute hepatopathy in these mice after Listeria monocytogenes infection. Our findings highlight a simple and noninvasive method to assess macrophage phagocytic function in vivo, which should be assessed in further murine and human studies as a tool for predicting host vulnerability to infection.